FUNGSI TARI BESOGAK DALAM UPACARA ADAT TENTOBUS DAYAK PESAGUAN DI KECAMATAN TUMBANG TITI KABUPATEN KETAPANG - Dekapriyo, Fernandus Deo; Ismunandar, Ismunandar; Satrianingsih, Aline Rizky Oktaviari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research background was based on the researcher's interest when watching the performance of traditional ceremonial in Tumbang Titi Sub-District Ketapang District. Seeing from the part of the process in Tentobus traditional ceremony, one of them was Tari Besogak. Tari Besogak has meanings in the dance and it contained honorable value of life between the Dayak Pesaguan society. In the beginning, there were many people of Dayak Pesaguan in Tumbang Titi Sub-District that believe Tari Besogak was only a mere show. Therefore, this research intended to know the function of Tari Besogak in Tentobus traditional ceremony of Dayak Pesaguan in Tumbang Titi Sub-District Ketapang District. This research was using qualitative research method using anthropology approach. The data collection technique was interview and documentation study. Tentobus ceremony functioned as bad reinforcements rejection and redemption that had been done in the past. Based on the results of this researcher, it could be concluded that the function of Tari Besogak was as one of ceremony process to reject bad reinforcements. Tari Besogak as a ceremonial dance had characteristics such as the chosen dancers, offerings, outfits, place, and time that had been decided.